2011
DOI: 10.5194/acp-11-2145-2011
|View full text |Cite
|
Sign up to set email alerts
|

Three-year ground based measurements of aerosol optical depth over the Eastern Mediterranean: the urban environment of Athens

Abstract: Abstract. Three years (2006)(2007)(2008) of ground-based observations of the Aerosol Optical Depth (AOD) in the urban environment of Athens, in the Eastern Mediterranean, are analysed in this work. Measurements were acquired with a Multi-Filter Rotating Shadowband Radiometer at five wavelengths. The daily average AOD at 500 nm is 0.23, and the meanÅngström coefficient calculated between 415 and 867 nm is 1.41. The annual variability of AOD has a spring maximum dominated by coarse dust particles from the Sahara… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
65
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(73 citation statements)
references
References 65 publications
8
65
0
Order By: Relevance
“…Maximum AODs are found in summer, as already reported in the scientific literature for the Athens metropolis (e.g. Gerasopoulos et al, 2011) as well as at different midlatitude locations (e.g. Chey- (Student, 1908) and the nonparametric Mann-Kendall trend test (Mann, 1945;Kendall, 1938) all gave statistically significant results (Student's t test: t value = 4.31471, p value < 0.0001, N = 924; Mann-Kendall test: τ statistics = 0.124, 2-sided p value < 2.22 × 10 −16 ).…”
Section: Radiometric Stabilitysupporting
confidence: 67%
See 1 more Smart Citation
“…Maximum AODs are found in summer, as already reported in the scientific literature for the Athens metropolis (e.g. Gerasopoulos et al, 2011) as well as at different midlatitude locations (e.g. Chey- (Student, 1908) and the nonparametric Mann-Kendall trend test (Mann, 1945;Kendall, 1938) all gave statistically significant results (Student's t test: t value = 4.31471, p value < 0.0001, N = 924; Mann-Kendall test: τ statistics = 0.124, 2-sided p value < 2.22 × 10 −16 ).…”
Section: Radiometric Stabilitysupporting
confidence: 67%
“…Aerosol conditions in Athens have been addressed in previous studies and have been found to range from relatively clean maritime conditions to long-range desert dust transport episodes, smoke advection from forest fires and small particles typical of an urban and industrialised environment (e.g. Pissimanis et al, 1994;Eleftheriadis et al, 1998;Colbeck et al, 2002;Adamopoulos et al, 2007;Tsaknakis et al, 2011;Kaskaoutis et al, 2007;Kosmopoulos et al, 2008;Liu et al, 2009;Gerasopoulos et al, 2011;Amiridis et al, 2012).…”
Section: Experimental Sitementioning
confidence: 99%
“…These meteorological patterns govern the transport of aerosols released from various sources around the Mediterranean region and lead to a maximum aerosol load during the summer (Monks et al, 2009;Nabat et al, 2013). Moreover, a mixture of different sources is usually observed due to the long-range transport of the associated particles (Dall'Osto et al, 2010;Gerasopoulos et al, 2011;Boselli et al, 2012). Due to these complex characteristics, the specific impact of each aerosol source cannot be easily assessed.…”
Section: Introductionmentioning
confidence: 99%
“…According to the study of this region by Gerasopoulos et al (2011), in the summer period, the build-up of particles due to intense photochemical processes favored by high temperature and insolation contributes to elevated AOD levels in a way that reflects the geographical spread of particle precursor sources and transport processes. In comparison, the average (2006)(2007)(2008) summer AOD (at 500 nm) is 0.22 (0.27 at 440 nm), and this value is exceeded during four consecutive days during the measurement period (17-20 July) either due to the presence of dust (e.g.…”
Section: Aerosol Variability During the Experimentsmentioning
confidence: 99%